Proteasome inhibitors related thrombotic microangiopathy: a systematic and comprehensive review - Can Chen; Yiwei Li; Pengfei Shi; Shenxian Qian (Blood Cancer Journal)
Abstract Proteasome inhibitors (PIs) are crucial in treating multiple myeloma but carry a risk of thrombotic microangiopathy (TMA), especially with carfilzomib use. This systematic review includes 44 studies with 115 cases of PI-induced TMA, where carfilzomib was implicated in 101 cases. Treatment approaches varied: 28 patients received supportive care, 43 underwent therapeutic plasma exchange (TPE), 9 were treated exclusively with eculizumab (ECU), and 13 received both TPE and ECU. Notably, eculizumab significantly improved outcomes for patients unresponsive to initial TPE, achieving complete remission in seven cases. The need for dialysis emerged as a significant predictor of outcomes, often indicating a poor prognosis. For patients suspected of having PI-TMA, it is advisable to discontinue the offending medication promptly, even without definitive laboratory confirmation. In cases where diagnosis is challenging, kidney biopsy may assist if conditions permit. Comprehensive evaluation of the complement system, including genetic mutations, function, and associated complement inhibitory factor antibodies, should be included in the assessment of PI-TMA. Early administration of eculizumab may be beneficial in cases of suspected complement abnormalities or suboptimal response to initial treatments.